Rancang Bangun Inverter Pure Sine Wave Full Bridge Menggunakan Arduino Nano Sebagai Pembangkit SPWM - Idris, Fahmi; Roza, Indra (Universitas Medan Area, 2023)
In the current rapid development of electronics, the use of Arduino microcontrollers is quite often used in electronic devices, one of which is an inverter. An inverter is a device that can convert direct electric current (DC) into alternating electric current (AC). To get a pure sine wave on the inverter, you can use a technique to modulate the width of the DC wave signal called SPWM (Sinusoidal Pulse Width Modulation), because of its advantages in producing low harmonic disturbances. This method is carried out by combining two square waves as a carrier signal of 10 KHz and a reference signal of 50 Hz. The reference signal and carrier signal are generated with the Arduino Nano microcontroller, by amplifying the SPWM signal using the IR2110 IC, so that it is able to carry out the switching process on the Full-bridge inverter circuit using the IRF3205 Mosfet component and the inverter voltage is increased by a 7V/220V 10A step-up transformer so that expected to produce an AC voltage of 220 V with a frequency of 50 Hz sine wave.